2006
DOI: 10.1071/ea04044
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Australian lucerne (Medicago sativa) germplasm to grazing by sheep

Abstract: The sheep grazing tolerance of a diverse range of lucerne germplasm (Medicago sativa subspp. sativa, falcata and caerulea) was investigated at Roseworthy in South Australia. Lucerne entries were established on a sandy loam soil in 1998 and managed with rotational grazing management for the first 12 months. Continuous grazing by sheep in the following year reduced the plant density of each entry as measured by plant frequency estimates by 2–98%. Lucerne was allowed to recover, then grazed continuously for anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…However, it has been shown that good grazing tolerance can also be obtained by appropriate germplasm choice and selection pressure in winter‐active germplasm with a ‘conventional’ growth habit (Bouton et al. , 1998; Humphries et al. , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that good grazing tolerance can also be obtained by appropriate germplasm choice and selection pressure in winter‐active germplasm with a ‘conventional’ growth habit (Bouton et al. , 1998; Humphries et al. , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Repeated defoliation with inadequate recovery leads to loss of dry matter production and reduces persistence. While cultivars have been developed that are more tolerant of frequent defoliation (Bouton, ; Humphries, Kobelt, Bellotti, & Auricht, ; Sewell, Hill, & Reich, ; Smith, Bouton, Singh, & McCaughey, ), this general principle still applies. Although recommendations exist regarding recovery periods following defoliation, evaluation of various recovery regimes in different environments is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, lucerne is poorly adapted to winter waterlogging (Hill, 1996), is sensitive to acidic soils and aluminum (Munns, 1965), and cannot tolerate continuous grazing (McKinney, 1974). The dryland cultivars of lucerne are selected based on survival during establishment, grazing tolerance (Humphries et al, 2006), general adaptation (Bouton, 2012) and persistence through drought conditions (Marshall et al, 2008). A key trait for the tolerance to water stress is the development of a large taproot in lucerne (Johnson and Tieszen, 1994).…”
Section: Introductionmentioning
confidence: 99%